The Family Principle in Economy: Understanding the Concept and Practical Challenge - Rizaldi, Arjuna (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
This research aims to delineate how the family principle has been regarded and understood in Indonesia's Economy. Furthermore, it seeks to comprehensively understand the family principle to prevent further misconceptions or multi-interpretations. The method used is the qualitative approach that is based on literary studies. Besides providing the advantage of being exploratory in nature, the approach is suitable for studies in the environment of economic theory as researchers attempt to gain understanding through the thoughts and interpretation building of significant figures in the Indonesian economy. Overall, it is evident that cooperation and competition are the two crucial and equally important elements of the family principle to understand the concept comprehensively. Thus, the research concluded that both concepts had been integrated into the family principle as coopetition, whereas all economic institutions recognized by the constitution simultaneously compete and cooperate.